Bidirectional Association Between Asthma and Obesity During Childhood and Adolescence: A Systematic Review and Meta-Analysis - Shan, Li-Shen; Zhou, Qian-Lan; Shang, Yun-Xiao (Frontiers in Pediatrics, 2020)
Objective Co-occurrence of pediatric asthma and obesity has been widely reported, yet the causal directions between these two disorders are still not well understood. The objective of this meta-analysis is to explore whether there was the possibility of a bidirectional association for these two disorders in children and adolescents. Methods PubMed, Embase, Web of Science and CENTRAL databases were searched up to August 2020. Cohort studies reporting the associations of obesity with risk of physician-diagnosed asthma, or physician-diagnosed asthma with risk of obesity in children and adolescents were eligible for the review. Results A total of 3091 records was identified from the four databases, with final inclusion of nine. Six studies reported the association between obesity and risk of asthma, three studies reported the association between asthma and risk of childhood obesity. As evaluated by the Newcastle-Ottawa quality assessment scale, all studies were assessed as high-quality studies. There was a statistically significant association between obesity and increased risk of physician-diagnosed asthma in children and adolescents. The pooled RR was 1.39 (95% CI: 1.28, 1.50; P < 0.001), with significant heterogeneity across studies (I2 = 81.7%; P heterogeneity < 0.001). The pooled RR in boys was 1.53 (95% CI: 1.17, 1.99; P = 0.002), but such a significant association was not observed in girls (RR=1.17, 95% CI: 0.79, 1.72; P = 0.434). For the association of asthma with risk of childhood obesity, the pooled RR was 1.47 (95% CI: 1.25, 1.72; P <0.001) without statistical heterogeneity (I2 = 0%, P heterogeneity = 0.652). Conclusion There is a bidirectional association between obesity and asthma during childhood and adolescence, suggesting that childhood obesity drives an increase in the onset of asthma, meanwhile childhood asthma may also increase risk of obesity for children and adolescents.